(untitled) (Ecological Bulletin of Kryvyi Rih District, 2019)
Protection and using of wild medicinal plants’ resources are issues of current interest in Ukraine. The problem of reproduction of their natural resource potential and rational use is particularly acute. An important condition of non-exhausting using of phytoresources is studying of their species composition, structure of natural populations, opportunities for harvesting, restoration of raw material resources in natural growing conditions. Despite rapid development of chemistry and increasing a number of new, more eﬀective synthetic pharmaceuticals, antibiotics, medicinal plants continue to occupy an important place in a range of medicines. The use of medicinal plants in folk and contemporary medicine has a multi-year tradition. The medicines of plant origin are characterized with low toxicity and minor allergic reactions in comparison with synthetic compounds. All this issues are of current interestand very important in school practice and hould be realized in subjects that promotes conformity to through content line of biology program «Health and Security».